Introduction to cataloging and the classification of books - Mann, Margaret; American library association (Chicago, Ill. : American library association, 1930)
It is an attempts to orient the student of library science in the problems presented by books, as well as in the means used to make them of service to readers.
Includes bibliographical references and index.
rpm 25/01/2019
Loans
Keywords: Cataloging